Realização de trabalhos de laboratório online e utilização de materiais auto-normalizantes no ensino à distância - Rocha, Junia Magalhães (2009)
This study has, as its objective, the proposal of alternative ways of taking Distance Graduation Courses, emphasizing their quality. This theme is relevant in the academic circle because it discusses improvements in teaching methods based on the use of Self Normalizing Materials and the practicability of online laboratories. These addendum have as an objective the guaranteeing of student opportunities, opening up frontiers and contributing to the democratization of teaching. It is hoped that these proposals will make it possible to improve the quality of distance learning, permitting student development with practical experiences and, with the material utilized, making it possible to increase in knowledge while reducing the possibility of failures.